2018
DOI: 10.4317/medoral.22617
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus is not detected in mucosal lichen planus

Abstract: BackgroundLichen planus (LP) is a chronic inflammatory, immunological, mucocutaneous disease can affect skin, genital and oral mucosa. Oral lichen planus (OLP) is the most common noninfectious, chronic inflammatory oral disease affecting 1-2% of the general adult population. World Health Organization (WHO) classifies OLP as a potentially malignant disorder. Epstein Barr virus or human herpesvirus-4, is a member of the herpes virus family and one of the most ubiquitous viruses known to human, infecting approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The general characteristics of the included studies are summarized in Table 1. Ten case‐control studies 13‐16,20‐23,28,29 comprising 690 subjects (386 OLP cases and 304 healthy controls) were included in the present review; of these, 8 studies were eligible for the meta‐analysis 13‐16,20,21,28,29 . The studies were published between 1996 and 2018.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The general characteristics of the included studies are summarized in Table 1. Ten case‐control studies 13‐16,20‐23,28,29 comprising 690 subjects (386 OLP cases and 304 healthy controls) were included in the present review; of these, 8 studies were eligible for the meta‐analysis 13‐16,20,21,28,29 . The studies were published between 1996 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in Sweden, 16,23 two studies in Iran, 20,22 one study in Denmark, 13 one study in Turkey, 14 one study in Ireland, 29 one study in Hungary, 15 one study in Brazil, 15 and one study in India 28 . Seven studies 13,15,16,20‐23 reported gender of the participants, in which females comprised two thirds of subjects. The age of the included participants ranged between 18 and 81 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Infectious factors can also result in immune abnormalities [67]. Hepatitis C virus [68,69] and human herpesvirus 6 [70,71] are associated with both OLP and HT, while other studies have reported conflicting results regarding the association of Epstein-Barr virus [72,73] and Helicobacter pylori [74,75] with these diseases.…”
Section: Environmental Factors Environmental Factors Play Anmentioning
confidence: 99%